Elite defection and grassroots democracy under competitive authoritarianism: evidence from Burkina Faso. Issue 4 (19th May 2019) - Andrews, Sarah; Honig, Lauren
ABSTRACT: One determinant of the success or failure of political revolutions is whether there is a split among the ruling elites. Elite defections in a competitive authoritarian regime can tip the balance in favour of regime change and democratization. This article examines when and why elites defect through the case of Burkina Faso. In October 2014, President Blaise Compaoré of Burkina Faso was forced to step down after 27 years in power and multiple term limits contraventions. We propose a new theory linking growth in democratic attitudes at the grassroots to elite defection from hegemonic parties. We argue that a broad increase in popular democratic attitudes can both decrease the costs and increase the benefits of elite defection, creating conditions that enable elites to rescind their loyalty to the regime. We support this argument with interviews with ruling-party defectors in Burkina Faso and two rounds of Afrobarometer survey data. Our findings demonstrate that democratic attitudes can grow under competitive authoritarian regimes, and that these citizen attitudes can impact regime change by increasing the likelihood of elite defection.